Non-Primary Basic Subject - Neelameghan, A. (Journal of Information and Knowledge, 1973)
The formation, recognition, and arrangement in a helpful sequence of Non-Primary Basic Subjects, Secondary Basic Subjects of various orders and Compound Basic Subjects of several varieties are discussed.